Early Childhood Educators' Self-Efficacy in Science, Math, and Literacy Instruction and Science Practice in the Classroom. Issue 1 (2nd January 2018) - Gerde, Hope K.; Pierce, Steven J.; Lee, Kyungsook; Van Egeren, Laurie A.
ABSTRACT: Research Findings: Quality early science education is important for addressing the low science achievement, compared to international peers, of elementary students in the United States. Teachers' beliefs about their skills in a content area, that is, their content self-efficacy is important because it has implications for teaching practice and child outcomes. However, little is known about how teachers' self-efficacy for literacy, math and science compare and how domain-specific self-efficacy relates to teachers' practice in the area of science. Analysis of survey and observation data from 67 Head Start classrooms across eight programs indicated that domain-specific self-efficacy was highest for literacy, significantly lower for science, and lowest for math. Classrooms varied, but in general, engaged in literacy far more than science, contained a modest amount of science materials, and their instructional support of science was low. Importantly, self-efficacy for science, but not literacy or math, related to teachers frequency of engaging children in science instruction. Teachers' education and experience did not predict self-efficacy for science. Practice or Policy: To enhance the science opportunities provided in early childhood classrooms, pre-service and in-service education programs should provide teachers with content and practices for science rather than focusing exclusively on literacy.